The impact of formative assessment on student achievement: A study of the effects of changes to classroom practice after a comprehensive professional development programme. (June 2017) - Andersson, Catarina; Palm, Torulf
Abstract: A random sample of 22 Year 4 teachers in mathematics from a middle-sized Swedish municipality participated in a teacher professional development programme in formative assessment. The content of the programme was formative assessment conceptualised as a unity of different, integrated strategies. The study examines the effects on student achievement of the changes in the teachers' formative classroom practice that followed the professional development input. Results show that, after controlling for pretest scores, the classes in the intervention group significantly outperformed the classes in the control group in a posttest administered one school year after the end of the programme (p = 0.036, d = 0.66). The study contributes to the understanding of under-studied areas of the impact of professional development in formative assessment, and the impact of teacher practice based on formative assessment conceptualised as a unity of different formative assessment strategies. Highlights: A random sample of teachers participated in a professional development program, PDP. We studied the impact of the PDP in formative assessment on student achievement. The classes of the teachers in the PDP outperformed the classes in a control group.